A novel approach for the analysis of engineering complex system accidents: The casualty of the M/V Vitaspirit. (15th May 2023) - Ceylan, Bulut Ozan; Elidolu, Gizem; Arslanoğlu, Yasin
Abstract: Modern sociotechnical engineering systems are comprised of dynamic and complicated man-machine-software interactions. These complex systems, such as ships, also pose a wide range of catastrophic risks. In this study, a real ship casualty that occurred in recent years was analysed using the rule-based Fuzzy Failure Modes and Effects Analysis (FFMEA). FMEA is a risk analysis technique applied before the event; however, it has been used in this paper as an accident analysis tool by handling its limitations in a fuzzy environment. A bulk carrier case was evaluated by revealing its 15 root causes with expert judgment. Then, the most critical factors are found as poor situational awareness about ship technical specifications (R7), delayed notification of the main engine cooling water leakage to the bridge (R5), and lack of reporting about the failure cannot be repaired without stoppage of the main engine (R6). Furthermore, RPN and FRPN outputs were compared and corrective actions for the critical factors offered. The purpose of this research is to demonstrate that the rule-based FFMEA is an effective method that can be applied in the accident analysis process. The findings of the study can provide significant perspectives for stakeholders to take risk-reduction measures at both onboard and company levels. Highlights: This study utilizes FMEA with an innovative perspective by utilizing an accident analysis tool. A real ship casualty in recent years is selected and analysed with a rule-based fuzzy FMEA method. The outputs of RPN and FRPN were compared, and correction measures were proposed. The most critical factor for the accident is found poor situational awareness about ship technical specifications.